Filsafat Ilmu Filsafat ilmu sebagai dasar pola pikir ilmiah di era digital: Menanamkan kesadaran kritis dalam arus informasi dan teknologi modern - nugroho, cahyo - (Maliki Interdisciplinary Journal, 2025)
Advances in digital technology have revolutionized the way humans access and manage information. However, the flow of information in the digital era also brings challenges to people's scientific and critical thinking skills. This article discusses the role of philosophy of science in shaping a rational, structured and reflective mindset in the midst of information disruption. Through epistemological approaches and scientific logic principles such as verification and falsification, philosophy of science becomes an important foundation in fostering critical awareness, especially for the younger generation who are vulnerable to instant information and algorithmic bias. This article also emphasizes the urgency of philosophy of science education since the secondary level as a strategy to build analytical skills and ethical thinking in the post-truth era. Thus, philosophy of science serves as an instrument of intellectual transformation in creating an informed and responsible digital society.